Assessment of functionalized iron oxide nanoparticles in vitro: introduction to integrated nanoimpact index. Issue 4 (30th August 2015) - Bayat, N.; Lopes, V. R.; Sanchez-Dominguez, M.; Lakshmanan, R.; Rajarao, G. K.; Cristobal, S.
<x xml:space="preserve">Abstract</x> The integrated nanoimpact index (INI) is an early warning scale of nano-impact based on a combination of toxicological end points and can be helpful in assessing the risks of exposure of any novel engineered nanoparticle such as the SPIONs presented here.